Revenues And Productivity of Romanian Agriculture: A Brief Analysis 2021 - Beatrice-Simona MANOLACHE; Silviu Cristian SIMIONESCU; Silvius STANCIU (Communications of International Proceedings, 2023)
The paper focuses on analyzing the relationship between revenue and productivity of employees in the agricultural sector in Romania in 2021. The analysis of the data of the National Institute of Statistics revealed an interesting correlation between the income and productivity of the employees in the agricultural sector in Romania. Agricultural companies that invest in employee training and improving production processes can achieve higher income. Additionally, business strategies aimed at improving employee productivity and increasing revenue can have a significant impact on the performance of agricultural enterprises. Based on these results, agricultural companies in Romania should pay special attention to the development and training of human resources, as well as the optimization of production processes, in order to improve productivity and obtain higher revenues. In addition, it is important that the government provides more support in developing training programs and promoting investment in technology and equipment for agricultural enterprises. Agriculture is an important component of the global economy, being responsible for producing and supplying food and other essential resources for human society. The research has shown that increasing the performance and productivity of human resources of companies is necessary to sustain and improve the sustainability of the Romanian agricultural sector.
Keywords: agriculture; companies; income; productivity; human resources; Romania